PEMIKIRAN IMAM SYAFI’I TENTANG ALQUR’AN, TAFSIR DAN TA’WÎL - Tsalis Muttaqin (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2014)
Imam Syafi'i was a great muslim scholar who was born inthe second century AH (Anno Hegirae). He was known for hisgreatness and his intellectual ability, so that many muslim scholarsfollow his thoughts in the field of Islamic jurisprudence (Fiqh). InIndonesia, Many muslims follow mazhab of Imam Syafi'i and it is thethe most popular mazhab in the country. As his popularity in the fieldof Fiqh, he was also an expert in the field of tafsir and ta'wil. It issurely that Imam syafi‟i had special attention to the Qur'an, tafsir andta'wil. The books written by Shafi'i were also talking about Qur'an,tafsir and ta'wil. Most of his books talked about the issues on fiqh andushul fiqh, because both are the focus of his study. His thoughts aboutthe Quran, tafsir and ta'wil had flown into pieces. This article tries todescribe some of his thoughts about the Quran, tafsir and ta'wil. It isvery important topic to describe because the contributions of ImamSyafi'i in the field Quran, tafsir and ta'wil having the great influenceamong muslim scholar.